Cohesive and adhesive failure of hard and brittle films on ductile metallic substrates: A film thickness size effect analysis of the model system hydrogenated diamond-like carbon (a-C:H) on Ti substrates. (15th January 2015) - Bernoulli, D.; Häfliger, K.; Thorwarth, K.; Thorwarth, G.; Hauert, R.; Spolenak, R.
Abstract: Using the model system hydrogenated diamond-like carbon (a-C:H) on titanium (Ti) substrates the effect of a changing film thickness on the cohesive and adhesive failure of hard and brittle films on ductile metallic substrates is analyzed by uniaxial loading. A film thickness size effect has been observed for the fracture strength and the onset strain of delamination. For a a-C:H film thickness <1 μm the fracture strength increases significantly with decreasing film thickness while the change in fracture strength for thicker films is small. The total area of delamination has been determined by the delamination area ratio (DAR), a measure to quantify the delaminated area at a given strain. The DAR reveals a thickness and strain dependency for film thicknesses >1 μm, whereas for film thicknesses of 200 and 500 nm the effect of the strain is only secondary. Upon uniaxial loading the Ti substrate exhibits an anisotropic deformation which affects the cohesive and adhesive failure of thin a-C:H films. The energy release rates for cohesive and adhesive failure and the fracture toughness of a-C:H are all independent of film thickness. The corresponding values have been determined to be 63.5 ± 2.6 J m −2, 579 ± 20 J m −2 and 3.2 ± 0.1 MPa m 1/2, respectively. Finally, a schematic is presented to determine qualitatively the adhesion of ductile and moderately brittle films on any kind of substrate.